Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acsnano.7b03433
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Design of Three-Dimensional Ordered Tribrachia-Post Arrays with Re-entrant Geometry for Omniphobic and Slippery Surfaces

Abstract: Hydro- and oleophobic (namely, omniphobic) coatings or surfaces have many important applications, but tremendous challenges in fabrication aspects still remain. Herein, we report a bioinspired design and nanofabrication of three-dimensional (3D) tribrachia-post arrays with re-entrant geometry (3D TPARG) for superhydrophobic and oleophobic polymer films or surfaces. By simply controlling the temperatures and time to treat silica colloidal templates, we can readily fabricate 3D ordered polymer arrays of tribrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…Intriguingly, such reentrant structures are also observed on the surface of protein‐based nanoparticles, which provides protection against contamination . As such, reentrant design is essential for designing surfaces with antioil, anti‐biofouling, and anticorrosion functions …”
Section: Discovery: Natural Surfacesmentioning
confidence: 99%
“…Intriguingly, such reentrant structures are also observed on the surface of protein‐based nanoparticles, which provides protection against contamination . As such, reentrant design is essential for designing surfaces with antioil, anti‐biofouling, and anticorrosion functions …”
Section: Discovery: Natural Surfacesmentioning
confidence: 99%
“…Superomniphobic surfaces that can repel a wide range of liquids with high contact angle and low sliding angle have received increasing attention as they have versatile applications, including antibiofouling, 1,2 liquid transportation, 3,4 drag resistance reduction 5,6 and self-cleaning surfaces, [7][8][9][10] etc. Building such surfaces usually requires the combination of micronanostructured hierarchical surfaces and the subsequent treatment of low surface energy chemicals 11 The chemical treatment can be implemented by peruorocarbon materials onto structured surfaces, including vapor deposition [12][13][14][15] and dip-coating.…”
Section: Introductionmentioning
confidence: 99%
“…Building such surfaces usually requires the combination of micronanostructured hierarchical surfaces and the subsequent treatment of low surface energy chemicals 11 The chemical treatment can be implemented by peruorocarbon materials onto structured surfaces, including vapor deposition [12][13][14][15] and dip-coating. 7,8,[16][17][18] To make hierarchical micro/nano structures, methods such as stacking micro and nanospheres, 9,16 texturing bers, 17 and spray coating, 7,12,18,19 have been commonly used while fabrication of such surfaces with special surface topography such as nanopatterned micropillars, usually involves photolithography or reactive ion-etching using sophisticated tools with complex preparation process. [13][14][15][19][20][21][22][23][24] Recently, the unique structure observed on the skin of springtails has been reported to have extraordinary liquidrepellent characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is now well understood that negative slope shapes such as the re‐entrant profile of microstructures are critical factors in achieving robust and energetically favorable superomniphobic surfaces . More recently, several research groups effectively demonstrated omniphobic, liquid sliding and slippery surfaces by drawing inspiration from nature such as springtail, rice leaf, and pitcher plant . These liquid repellent surfaces have many practical applications, ranging from academia to precision industries such as microfluidics, electronic devices, oil–water separation system, and oil collecting or transportation area …”
mentioning
confidence: 99%